2018
DOI: 10.1111/odi.12963
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between body mass index and outcomes for patients with oral squamous cell carcinoma

Abstract: Obesity may contribute to a higher recurrence rate and a worse prognosis in OSCC patients than in normal-weight patients in northern China. However, underweight patients have a higher risk of postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
2
3
1
1
Order By: Relevance
“…Preventing a decline in the nutritional status prior to surgery could be a means to reduce these negative consequences. In another study, our team found that the incidence of complications after OSCC surgery was highest (33.3%) in the low BMI group, but no significant relationship between BMI and POCs was demonstrated in this study (14). This may be due to the stricter screening procedure before free flap reconstruction for patients enrolled in this study.…”
Section: Perioperative Factors (Operation Time and Antibiotic Prophyl...contrasting
confidence: 60%
See 2 more Smart Citations
“…Preventing a decline in the nutritional status prior to surgery could be a means to reduce these negative consequences. In another study, our team found that the incidence of complications after OSCC surgery was highest (33.3%) in the low BMI group, but no significant relationship between BMI and POCs was demonstrated in this study (14). This may be due to the stricter screening procedure before free flap reconstruction for patients enrolled in this study.…”
Section: Perioperative Factors (Operation Time and Antibiotic Prophyl...contrasting
confidence: 60%
“…Demographic factors (age, sex, Body Mass Index (BMI) and weight loss), tumor anatomy and pathological features (tumor site, T stage, pathological nodal [pN] stage, clinical features, and growth patterns) and operation-related variables (operation time, blood loss, intraoperative fluid, tracheostomy[yes/no], type of flaps used, ND (unilateral/bilateral), type of antibiotic prophylaxis and red blood cell (RBC) transfusion during the operation[yes/no]) were recorded. Based on World Health Organization (WHO) cutoff points of BMI status, BMI were categorized into obese (≥30.0 kg/m 2 ), overweight (25.0-29.9 kg/ m 2 ), normal weight (18.5-24.9 kg/m 2 ), and underweight (<18.5 kg/m 2 ) (14). Weight loss was defined as "weight loss >10% of the body weight within the past 6 months (21).…”
Section: Covariatesmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the phenomenon of "obesity paradox" is dominated in recent literatures 9 . It is believed that, poor nutritional intake and tumor cachexia might have contributed to low BMI documented in studies 18 . In present research, we found an association of low BMI with advanced stage tumor, which corroborates with recent data.…”
Section: Discussionmentioning
confidence: 99%
“…Penurunan berat badan merupakan salah satu gejala yang dikeluhkan oleh pasien pada penelitian lain. Indeks massa tubuh yang rendah juga dihubungkan dengan prognosis yang lebih buruk (Wang et al, 2019), (Li et al, 2015). Pekerjaan pasien terbanyak adalah buruh pabrik dan petani, hal ini berkorelasi dengan penelitian lain yang menyebutkan bahwa salah satu faktor risiko terjadinya KSS adalah riwayat paparan sinar matahari dalam jangka waktu lama (Sari et al, 2021).…”
Section: A Pembahasanunclassified